The ECLiPSE Procedure as an Alternative to Mastopexy following Implant Removal. Issue 7 (27th July 2021) - Wilssens, Nicholas; Singla, Apresh; Hoffman, Stuart; Graham, Susannah; Jayatilleke, Nipu; Lajevardi, Sepehr; Barker, Anthony; Deva, Anand K.
Abstract : Background: With the rise in number of breast implant removals for a variety of indications, strategies to improve aesthetic outcomes, while minimizing scars and operating time, will prove to be of benefit. We present here a novel periareolar sickle skin excision as a good option for women with mild to moderate ptosis and central loss of breast volume following implant removal/capsulectomy. Methods: The ECLiPSE ( E xplant, C apsulectomy, Li ft using P eriareolar S ickle skin E xcision) was utilized in 53 patients with a median follow-up of 24 weeks. Results: The majority of these patients had breast implants for cosmetic augmentation and the most common indication for implant removal was capsular contracture (n = 47, 88.7%). Forty-six patients (86.8%) scored a high or very high satisfaction with the outcome of the procedure. Conclusion: We believe that the ECLiPSE procedure is a useful option that can produce a reasonable aesthetic outcome following implant removal/capsulectomy while minimizing visible scarring.